Use of Technology in Audit - Bibicheva, Tatiana (2021)
Process automation is one of the crucial priorities of almost each company in the current time and audit firms are not an exception. Since the time when first calculating machines were used to ease human work in terms of data processing and evaluation, many tools have been developed and implemented into day-to-day activities both on personal and firm levels. Thus, we have an opportunity to observe this trend, undertake an attempt to understand it, use it in our work, modify and improve. With such an eternal development process, it is highly important to follow it and not to be lost in this way, especially in the time when efficiency and effectiveness are key goals of modern society. This thesis aims to focus on such trends in relation to audit, identify the development curve, its current status and prospective. It will provide a reader with the most updated information including examples and professional opinions of people involved in audit engagements and having experience with the newest technological achievements.